2004
DOI: 10.1111/j.1600-4469.2004.00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Are all mouthguards the same and safe to use? The influence of occlusal supporting mouthguards in decreasing bone distortion and fractures

Abstract: The safety benefits of mouthguards have been demonstrated in many studies, with many authors and sports dentists strongly recommending the wearing of mouthguards. However, wearing a mouthguard with incorrect occlusion might cause a variety of problems. It comes as no surprise that a traumatic blow to the chin, while wearing an insufficient mouthguard lacking anterior contact, can result in severe distortions to the mandibular bone, and bone fractures. The aim of this study was to clarify how ineffective insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 13 publications
(23 reference statements)
2
36
0
3
Order By: Relevance
“…Similar to our findings, previous studies have reported that athletes who use custom mouthguards are more likely to be informed of the benefits, indications, and properties of the mouthguard by their dentist [22,23]. Kenyon and Loos compared custom and boil-and-bite mouthguards in terms of comfort, use, adjustment, and patient preferences.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar to our findings, previous studies have reported that athletes who use custom mouthguards are more likely to be informed of the benefits, indications, and properties of the mouthguard by their dentist [22,23]. Kenyon and Loos compared custom and boil-and-bite mouthguards in terms of comfort, use, adjustment, and patient preferences.…”
Section: Discussionsupporting
confidence: 76%
“…Effective protection is the objective pursued by every athlete who purchases a mouthguard. There is a universal belief that thicker protectors provide more security while also being more uncomfortable, a belief that influences athlete preference [22]. In many cases, this belief is the result of advertising, which affects whether an athlete will purchase an established protector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the mouthguard is cut and trimmed completely, occlusion is adjusted on the articulated model to prevent the mouthguard from becoming distorted. This mouthguard should offer fully balanced occlusion and good protection against direct impact, the most common type of impact, except in sports such as American Football, where damage is more likely to arise from horizontal impact due to use of a faceguard (30) (Fig.9). …”
Section: Methodsmentioning
confidence: 99%
“…Bu artış, birçok yararlı etkilerinin beraberinde potansiyel yaralanma riskini de beraberinde getirmektedir 18,19 . Bu nedenle, spor ile ilgili yaralanmaların sayısının ve şiddetinin azaltılmaya çalışılması önemli bir hedef haline gelmiştir.…”
Section: Tartiġmaunclassified